Mysticism in the Kyai Brojomusti Folklore and Its Pedagogical Relevance: A Literary-Ecological Analysis - Rahmawati, Pramesti Icha; Lestari, Sri (Media Publikasi Cendekia Indonesia, 2025)
This study investigates the mystical elements contained in the folklore of the Kyai Brojomusti forbidden forest and examines their relevance for Indonesian language learning in secondary education. Previous studies have not sufficiently addressed the contribution of local folklore to classroom instruction and to the development of students' cultural awareness. This research employs a qualitative descriptive design with data collected through observation, in-depth interviews, and documentation. The data are analyzed using a literary ecology framework. The findings identify three central concepts of mysticism in the Kyai Brojomusti narrative: positive motives, material existence, and levels of sarengat. The study also identifies six manifestations of mysticism, namely religious rituals, slametan or bancaan practices, healing practices, sacred trees, sacred tombs, and white tigers. These findings demonstrate that local folklore can function as a culturally grounded learning resource that supports value-based instruction and contributes to the development of the Pancasila student profile.